PERUBAHAN PILIHAN MASYARAKAT DARI PARTAI DEMOKRAT DALAM PEMILIHAN UMUM LEGISLATIF 2014 DI NAGARI TANJUANG BALIK KECAMATAN PANGKALAN KOTO BARU KABUPATEN LIMA PULUH KOTA SUMATERA BARAT - Ariyoni, Sepri; Tinov, M.Y.Tiyas (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
At the level of Representatives Legislative elections in 2009 at district Pangkalan Koto Baru won by Demokrat with the acquisition of 3781 voices, then in 2014 Demokrat just earn 2921 votes. The decreasing of the voices of Demokrat occurred at Nagari Tanjuang Balik was 323 votes. This research aims to determine what factors are causing the public does not choose Demokrat in legislative elections in 2014 at Nagari Tanjuang Balik.This research use qualitative descriptive method. The respondents in this research were people who did not voted Demokrat in 2014 that 10% of 323 is 30 peoples. The technique of collecting data through interviews and questionnaires. Then the data processing techniques with qualitative methods.From the results of this research is that the factors that causing people did not vote for Demokrat in 2014 was a sociological, psychological, and rational choice (rational choice). It is known that the most dominant factor is the rational choice in which 27 people (90%) of respondents said the reason they have not choose Demokrat was the corruption that afflicts the candidate of Demokrat. The respondents considers that if they choose Demokrat again, then the chosen candidates would be afflicted by corruption.Keywords: Option Changing, Demokrat Party, Legislative Election